THE EFFECT OF BRAND ORIGIN, BRAND AWARENESS, BRAND PERSONALITY, AND BRAND IMAGE TOWARD PURCHASE INTENTION ON LOCAL BEER BRAND (STUDY ON POTENTIAL CONSUMER OF BEER BINTANG â€œRADLERâ€ IN MALANG CITY) - Ristanto, M. Bisma Rian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to examine the influence of the four variables that consist of Brand Origin, Brand Awareness, Brand Personality, and Brand Image on the evaluation on Purchase Intention either partially and dominant on potential consumer of beer Bintang â€œRadlerâ€ in Malang city. The type of research is explanatory research. ThisÂ research was conducted in Malang city. There are 110 questionnaires distributed to every consumer who has known and bought beer Bintang â€œRadlerâ€. The samplingÂ technique was purposive sampling and the research instruments were tested using Validity Test, Realibility Test and Classical Assumption Test. The data analysis testing used Multiple Regression Analysis. The hypothesis testing used was T test. Result showed that Brand Origin, Brand Awareness, Brand Personality and Brand Image influence consumer intention significantly to purchase beer Bintang â€œRadlerâ€ in partially. Therefore, Brand Personality is the dominant factor in creating consumer purchase intention. Keywords: Brand Origin, Brand Awareness, Brand Personality, Brand Image, Purchase Intention, Beer Bintang, Radler